THE DIFFERENCE OF LEARNING ACHIEVEMENT USING COOPERATIVE LEARNING MODEL APPLIED ON THE GRADE VIII STUDENTS OF SMP NEGERI 1 KOLAKA - Supratman Supratman; St. Rahma (Universitas Sembilanbelas November Kolaka, 2017)
The design of this research was experiment and aimed to know whether there was difference of learning result of mathematics between students taught by using cooperative learning model type TSTS, NHT, and STAD. The population in this study was all students of class VIII SMP Negeri 1 Kolaka academic year 2015/2016 while the sample taken was by Cluster Random Sampling technique. Techniques of collecting data used test and observation technique. To get a representative test, the validity and reliability test were conducted. The data obtained were analyzed using normality test, homogeneity test, and One Way Anova test. From the analysis result, it was found that the initial analysis for normality test at 5% level (n = 26) obtained Dtabel = 0,264 while Dcount = 0.0975 (experiment class I) Dcount = 0.1668 (experiment class II) and Dcount = 0.1451 (control class), Because Dcount Dtable then H0 was accepted so the data was normally distributed. For homogeneity test at 5% level (n = 78) obtained F (0.05, 2, 75) = 3.12 and L = 2.364 Since L Ftable then H0 was accepted so the data was homogeneous. With One Way Anova test obtained Fcount = 13.427 and at 5% level obtained (2:75) Ftable = 3.12 for Fcount Ftable then H1 was accepted so there were differences in learning outcomes between students taught using cooperative learning model type TSTS, NHT and STAD. Since H1 was accepted then a further test was conducted using scheffe t test. At level of 5% (dk = 50) obtained ttable = 2.0085 and tcount = 5.181. Â Because tcount ttable then H1 was accepted so the mean result of students' mathematics learning taught by model of cooperative learning type TSTS was better than mean result of cooperative learning type STAD. At 5% level (df = 50) obtained ttable = 2.0085 and tcount = 2.6429. Because tcount ttable then H1 was accepted so the mean result of students' mathematics learning taught by model of cooperative learning type NHT was better than cooperative learning type STAD. At level 5% (df = 50) obtained ttable = 2.0085 and tcount = 2.5387. Because tcount ttable then H1 was accepted so the mean result of students' mathematics learning which was taught by cooperative learning model of TSTS type was better than mean of mathematics learning result of student taught by NHT type.